London's burning [ true adventures on the frontlines of punk, 1976-1977 - Thompson, David , 1960- (Distributed by Independent Publishers Group, 2009)
The summer of 1976 through the summer of 1977 was the most significant year in British rock history. This collection of memories of concerts and cultural flash points focuses on what was happening on